Correction: Green synthesis of nitrogen-doped multiporous carbons for oxygen reduction reaction using water-caltrop shells and eggshell waste. Issue 30 (21st May 2021) - Hsu, Chun-Han; Pan, Zheng-Bang; Qu, Hau-Ting; Chen, Chuan-Ren; Lin, Hong-Ping; Sun, I-Wen; Huang, Ching-Ying; Li, Chun-Han
Abstract : Correction for 'Green synthesis of nitrogen-doped multiporous carbons for oxygen reduction reaction using water-caltrop shells and eggshell waste' by Chun-Han Hsu et al., RSC Adv., 2021, 11, 15738–15747. DOI: ; 10.1039/D1RA02100A .